2016
DOI: 10.1111/jace.14416
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Nanostructured Fluorine‐Doped Hydroxyapatite Coating from Aqueous Dispersion by Suspension Plasma Spray

Abstract: In this study, we prepared an aqueous dispersion of fluorine‐doped hydroxyapatite (FHA) nanoparticles by a wet chemical method. For the first time, the as‐prepared aqueous dispersion of FHA nanoparticles was directly used as suspension for depositing nanostructured FHA coating on stainless steel substrate by suspension plasma spray (SPS) method. Field‐emission scanning electron microscopy images confirm that the coating was nanostructured. X‐ray Diffraction pattern, Fourier‐transform infrared spectroscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Ultrasonic spray method can make the liquid with higher initial kinetic energy uniformly dispersed in another reaction solution, reduce the aggregation of hydroxyapatite, and improve the dispersion of nanoparticles. [10][11][12] Some organic compounds, such as amino acids, gelatin and oxalic acid, can be directly absorbed by bone tissue to promote the growth of bone tissue. As the basic unit of protein, amino acids are easily absorbed by the human body and have a certain promotion effect on bone growth.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic spray method can make the liquid with higher initial kinetic energy uniformly dispersed in another reaction solution, reduce the aggregation of hydroxyapatite, and improve the dispersion of nanoparticles. [10][11][12] Some organic compounds, such as amino acids, gelatin and oxalic acid, can be directly absorbed by bone tissue to promote the growth of bone tissue. As the basic unit of protein, amino acids are easily absorbed by the human body and have a certain promotion effect on bone growth.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many studies on improving the corrosion resistance of magnesium alloy by fluoride treatment. Such as MgF 2 conversion coatings, fluorine‐doped hydroxyapatite coatings (FHA), and fluorozirconate conversion coatings . All of these studies have shown that fluorine coatings on magnesium and its alloy can significantly reduce the biodegradation rate of magnesium and its alloy.…”
Section: Introductionmentioning
confidence: 99%